New Crystal Preferred Orientation of Amphibole Experimentally Found in Simple Shear. Issue 22 (29th November 2019) - Kim, Junha; Jung, Haemyeong
Abstract: The crystal preferred orientation (CPO) of amphibole has a large effect on seismic anisotropy in the crust. Previous studies have reported four CPO types (I–IV) of amphibole, but the genesis of type IV CPO, which is characterized by [100] axes aligned in a girdle subnormal to the shear direction, is unknown. In this study, shear deformation experiments on amphibolite were conducted to find the genesis of type IV CPO at high pressure (0.5 GPa) and temperature (500–700 °C). The type IV CPO was found under high shear strain ( γ > 3.0), and the sample exhibited grains in a range of sizes but generally smaller than the grain size of samples with lower shear strain. The seismic anisotropy of type IV CPO is lower than that of types I–III. The weak seismic anisotropy of highly deformed amphibole could explain weak seismic anisotropy observed in the middle crust. Plain Language Summary: Amphibolite is one of the major constituent rocks of the middle to lower crust and amphibole is a major constituent mineral of amphibolite. The crystal preferred orientation (CPO) of amphibole has a large effect on seismic anisotropy in the crust. In many previous studies on natural amphibolites, four amphibole CPO types (types I–IV) were observed. Types I, II, and III CPOs were found in previous deformation experiments at a pressure of 1 GPa, but the genesis of type IV CPO is unknown. In this study, shear deformation experiments on amphibolite were conducted at a high pressure (0.5 GPa) and temperature (500–700 °C) to find the origin of the type IV CPO. We found the type IV CPO of amphibole, for the first time, through deformation experiments under high shear strain (shear strain > 3.0), where the sample showed a wide range of grain size and/or small grain size. The type IV CPO of amphibole shows smaller seismic anisotropy than those of other amphibole CPO types. Our result show that even highly deformed amphibolites can exhibit weak seismic anisotropy. This weak seismic anisotropy of amphibole may be important to interpret the regional low seismic anisotropy in the middle crust. Key Points: We conducted shear deformation experiments on amphibolite at a pressure of 0.5 GPa and temperatures of 500‐700°C Type IV CPO of amphibole developed under high shear strain, where the sample showed wide range of grain sizes and/or small grain size Seismic anisotropy of amphibole for type IV CPO is weaker than for other CPO types